"Voorberei en toegerus": P.C. Potgieter se beskouing van die opleiding van predikante in kritiese perspektief - L. O. K. Lategan (Acta Theologica)
This article examines the training of ministers and interacts with the perspectives formulated by P.C. Potgieter. It considers Potgieter’s monograph on the theological curriculum, Voorberei en  toegerus, in which he outlines some characteristics of and conditions for theological training. In his opinion all theological training must be qualified by Scripture. Theological training should also create a sense for critical enquiry. Theological study is directed at the study of the Revelation of God and the church as the body of Christ. The article further discusses the literature on theological studies where attention is paid to the reasons for theological training, theology as a science and a priori assumptions in the study of theology. The article concludes with a discussion of Potgieter’s view on theological training.